Image_1.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Located along the western coastline of Mumbai’s northern suburbs, Madh Island is bound by the Arabian Sea to the west and Malad Creek to the east, which separates it from Versova. Commuters travelling between Madh and Versova use ferry services operating across Malad Creek. The first ferry starts at 5 am. Ferries run every 15 minutes, and the journey takes about five minutes. The ride fare is ₹3.00.